2007
DOI: 10.1103/physreva.75.033622
|View full text |Cite
|
Sign up to set email alerts
|

Nearly-one-dimensional self-attractive Bose-Einstein condensates in optical lattices

Abstract: Within the framework of a mean-field description, we investigate atomic Bose-Einstein condensates, with attraction between atoms, under the action of a strong transverse confinement and periodic [optical-lattice (OL)] axial potential. Using a combination of the variational approximation, one-dimensional (1D) nonpolynomial Schrodinger equation, and direct numerical solutions of the underlying 3D Gross-Pitaevskii equation, we show that the ground state of the condensate is a soliton belonging to the semi-infinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Such solitons were created in condensates of 7 Li [12] and 85 Rb [13] atoms, with the sign of the atomic interactions switched to attraction by means of the Feshbach-resonance technique (in the latter case, the solitons were observed in a post-collapse state of the condensate). In the presence of a periodic potential, such solitons should exist too, with the chemical potential falling in the semi-infinite gap of the spectrum, as first shown in the context of the optical setting [14], and later demonstrated in detail in the framework of GPEs [15,16,5].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Such solitons were created in condensates of 7 Li [12] and 85 Rb [13] atoms, with the sign of the atomic interactions switched to attraction by means of the Feshbach-resonance technique (in the latter case, the solitons were observed in a post-collapse state of the condensate). In the presence of a periodic potential, such solitons should exist too, with the chemical potential falling in the semi-infinite gap of the spectrum, as first shown in the context of the optical setting [14], and later demonstrated in detail in the framework of GPEs [15,16,5].…”
Section: Introductionmentioning
confidence: 91%
“…The NPSE including axial OL potential (3) was derived too [16,5], assuming the following factorization of the 3D wave function in Eq. (1),…”
Section: Bright Solitons In the Optical Latticementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, studies of quasi-two-dimensional (quasi-2D) BEC with embedded 2D potentials have drawn much interest [35,55]. In this connection, approximations which make it possible to reduce the underlying 3D Gross-Pitaevskii equation (GPE) to effective 1D [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] and 2D [62,63,65,66,[71][72][73][74][75][76] equations have been elaborated. In particular, different effective low-dimensional equations were developed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…However in a nice paper, Druten and Ketterle [6] consider the ideal gas in 1D and showed that with an appropriate choice of N and trap parameters BEC is possible; but the effect of interaction on the calculated properties was not discussed. The system of interacting bosons in 1D optical lattice and the study of different transport properties is another interesting area of research [7][8][9][10][11] both experimentally and theoretically. Although the low-lying excitation frequency in reduced dimension has been studied [11,12]; however, the thermodynamic properties of trapped bosons and their dependence on interaction are not yet studied in detail.…”
mentioning
confidence: 99%